Promotional Practices Among Micro Shea Butter Businesses in Northern Ghana - Issahaku, B. (University of Ghana, 2023)
This study adopts a qualitative research approach and the Technology-Organization-Environment theoretical lens to examine how shea butter micro-businesses in Northern Ghana use marketing communication tools to promote their offerings. The objective was to find out the specific promotion tools they used and to document the benefits and challenges these businesses face in promoting themselves. Using in-depth interviews and a focus group discussion, the study found that micro shea butter businesses use a combination of promotional mix elements. That is to say, these businesses weave in two or more tools of the promotional mix, which are, personal selling, advertising, public relations, and publicity among others in order to reach their target markets. Generally, their tendency is to shun traditional advertising in favor of online advertising.
MA. Communication Studies
Keywords: Technology-Organization-Environment; Micro Shea Butter Businesses; Ghana